Grounding Pancasila Values as Nusantara Character Building - Solin, Sahala Martua; Hasugian, Lisnawati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
Indonesia is increasingly showing a more civilized humanity through incessant social practices in times of pandemic pressure and natural disasters. Various difficulties experienced by all levels of society have raised the attention of others to help help in locations affected by the economic crisis and losing their jobs. Almost all lines are trying to push the values of Pancasila by the impulse of the cultural conscience of the people's wisdom. It seems that the movement of the ideological spirit by the residents has not yet been realized that the character building of Pancasila values is moving. Therefore, a phenomenological research is needed on the implementation of Pancasila values from government, institutional and community activities as character building. The purpose of this research is to prove that the values of Pancasila are the character of the Nation which is a reflection of National resilience. The research method used is the method of interview and observation to determine the qualitative awareness of understanding the values and their implementation that is being carried out by the community. The findings obtained are that the local community carries out social service activities to reduce the burden of food, clothing, shelter and economic congestion in the family to create psychological and life resilience. The second finding is that the public is increasingly aware of the power of citizen unity driven by the spirit of the Pancasila ideology among pluralist communities. From these findings, it is concluded that the values of Pancasila must be grounded through community coaching / learning activities with the colors of the characters and local wisdom according to the culture of the environment.